(untitled) (Journal of the Professional Association for Cactus Development, 2003)
Ten of the commercially most important cultivars of spineless cactus pear (Opuntia ficus-indica) were screened in the glasshouse and field for their susceptibility to four fungal pathogens (Phialocephala virens, Lasiodiplodia theobromae, Fusarium sp1 and Fusarium sp2) commonly associated with cladode and fruit diseases in South Africa during surveys conducted over the last three years. The fungi were artificially inoculated by means of toothpicks that had been colonised by the respective fungi prior to being inserted into the cladode or fruit. Control treatments consisted of sterile toothpicks. One trial was conducted with detached cladodes in the glasshouse and a second trial with cladodes of mature plants in a cactus pear orchard. A trial was also conducted with mature fruit of each cultivar in the laboratory. Following inoculation, cladodes and fruit were incubated at room temperature for 14 days to allow for lesion development around the inoculation site, whereafter, the diameters of lesions that resulted from inoculation were measured. In all three trials, considerable variation among cultivars in their susceptibility to each of the four pathogens was evident. Cladode inoculations in the glasshouse and field revealed that Nudosa and Algerian generally were the two most susceptible cultivars while Gymno Carpo, Zastron, and Malta generally were the most resistant. These results were consistent with those of inoculations conducted on fruit. Control treatments in all three trials did not develop lesions around inoculation wounds. Cluster analysis grouped cultivars into two clusters with Nudosa in its own cluster and the remaining cultivars in a second cluster.